Meeting Report from the Genomic Standards Consortium (GSC) Workshop 9. Issue 3 (November 2010) - Davidsen, Tanja; Madupu, Ramana; Sterk, Peter; Field, Dawn; Garrity, George; Gilbert, Jack; Glöckner, Frank; Hirschman, Lynette; Kolker, Eugene; Kottmann, Renzo; Kyrpides, Nikos; Meyer, Folker; et al.
Abstract This report summarizes the proceedings of the 9th workshop of the Genomic Standards Consortium (GSC), held at the J. Craig Venter Institute, Rockville, MD, USA. It was the first GSC workshop to have open registration and attracted over 90 participants. This workshop featured sessions that provided overviews of the full range of ongoing GSC projects. It included sessions onStandards in Genomic Sciences, the open access journal of the GSC, building standards for genome annotation, the M5 platform for next-generation collaborative computational infrastructures, building ties with the biodiversity research community and two discussion panels with government and industry participants. Progress was made on all fronts, and major outcomes included the completion of the MIENS specification for publication and the formation of the Biodiversity working group.